Mechanisms of Delayed Electrical Uncoupling Induced by Ischemic Preconditioning - Sandeep Jain; Richard B. Schuessler; Jeffrey E. Saffitz (2003)
Electrical uncoupling of cardiac myocytes during ischemia is delayed by ischemic preconditioning. This presumably adaptive response may limit development of arrhythmia substrates. To elucidate responsible mechanisms, we studied isolated, perfused rat hearts subjected to a standard preconditioning protocol of 3 cycles of 3 minutes of global no-flow ischemia each followed by 5 minutes of reperfusion before a 30-minute interval of ischemia. Changes in coupling were monitored by measuring whole-tissue resistance. Changes in phosphorylation and subcellular distribution of connexin43 (Cx43) were defined by quantitative immunoblotting and confocal microscopy. Preconditioning caused a 34% decrease in the maximal rate of uncoupling and delayed the time to plateau in uncoupling. Dephosphorylation of Cx43, known to occur during uncoupling induced by ischemia, was dramatically decreased in preconditioned hearts. Translocation of Cx43 from gap junctions to the cytosol, also known to occur during ischemia, was reduced by >5-fold in preconditioned hearts. The KATP channel blockers glybenclamide and 5-hydroxydecanoate prevented these effects in preconditioned hearts, whereas the KATP channel agonist diazoxide mimicked these effects in nonpreconditioned hearts. Intracellular translocation of Cx43 was blocked, but Cx43 dephosphorylation was not blocked during ischemia in preconditioned hearts treated with the PKC inhibitors chelerythrine and calphostin C. Uncoupling during ischemia was accelerated by PKC and KATP channel inhibition. Thus, delayed uncoupling in preconditioned hearts is likely related to diminished dephosphorylation and intracellular redistribution of Cx43 during prolonged ischemia. Both of these effects are regulated by activation of KATP channels, whereas PKC plays a role in internalization of Cx43.